Städtische Sportanlagen ein Wegweiser für den Bau von Spiel- und Sportgelegenheiten ; hrsg. im Auftr. d. Dt. Reichsaussch. f. Olymp. Spiele - Diem, Carl 1882-1962; Berner, Martin (Ullstein, 1914)
Sports facilities and stadiums planned for the 1916 Olympic Games that were to be held in Berlin.
Keywords: Olympic Games -- (6th : -- 1916 : -- Berlin, Germany); Olympic Games -- (6th : -- 1916 : -- Berlin, Germany) -- Facilities -- Planning; Olympics; Olympics -- Facilities; Sports facilities; Sports facilities -- Germany -- Planning; Deutschland